2021
DOI: 10.1109/access.2021.3064906
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Reliability Study of Grid-Connected PV Systems Using Evolutionary Computing Techniques

Abstract: Integrating renewable energy sources (RESs) into electrical power systems has gotten highly noticeable among researchers and those interested in electrical energy production due to the increase in energy demands, fossil fuel exhaustion, and ecological effects. PV-based renewable energy generation is one of the essential RESs that has appeared and had played a vital role in electrical power systems recently due to their advantages. In this regard, this paper presents a multi-objective computation problem for op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…As mentioned in the introduction, one of the main challenges of REPPs is their production uncertainty [2,3]. Although using the LWPF reduces this uncertainty, it cannot be ignored.…”
Section: ) Generation Uncertainty Of Lwpfmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction, one of the main challenges of REPPs is their production uncertainty [2,3]. Although using the LWPF reduces this uncertainty, it cannot be ignored.…”
Section: ) Generation Uncertainty Of Lwpfmentioning
confidence: 99%
“…Global warming, environmental pollutions and other destructive effects of fossil fuels-based power generation have led to a growing focus on the use of renewable energies around the world [1]. So, a growing trend can be seen in establishing and exploiting renewable energy power plants (REPPs) [2,3]. This type of power plants is usually integrated with the main grid to increase generation capacity with low pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Other works have considered how renewable resources may be essential to improving the resilience of power systems. In this context, some academics have indicated that the performance of PV systems and hybrid systems composed of wind, PV and batteries can increase operational efficiency and improve reliability and resilience after a natural disaster [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, since their generations of power is purely stochastic in nature (completely depend on climatic conditions which are extremely complex to be predicted accurately), and instances such as the technical connection failures, the set-up Renewable Energy Supply System (RESS) might experience frequent load failures or blackouts [3]. In other words, they are unable to guarantee a reliable and continuous supply of energy at a cost that can compete with the conventional power from the grid since the reliability level is highly influenced by the system's technical operation and the intermittency in the RES.…”
Section: Introductionmentioning
confidence: 99%